Mexican-origin women's individual and collective strategies to access and share health-promoting resources in the context of exclusionary immigration and immigrant policies - Alana M.W. LeBrón; Amy J. Schulz; Cindy Gamboa; Angela Reyes; Edna Viruell-Fuentes; Barbara A. Israel (BMC, 2024)
Abstract Background A growing literature has documented the social, economic, and health impacts of exclusionary immigration and immigrant policies in the early 21st century for Latiné communities in the US, pointing to immigration and immigrant policies as forms of structural racism that affect individual, family, and community health and well-being. Furthermore, the past decade has seen an increase in bi-partisan exclusionary immigration and immigrant policies. Immigration enforcement has been a major topic during the 2024 Presidential election cycle, portending an augmentation of exclusionary policies towards immigrants. Within this context, scholars have called for research that highlights the ways in which Latiné communities navigate exclusionary immigration and immigrant policies, and implications for health. This study examines ways in which Mexican-origin women in a midwestern northern border community navigate restrictive immigration and immigrant policies to access health-promoting resources and care for their well-being. Methods We conducted a grounded theory analysis drawing on interviews with 48 Mexican-origin women in Detroit, Michigan, who identified as being in the first, 1.5, or second immigrant generation. Interviews were conducted in English or Spanish, depending on participants' preferences, and were conducted at community-based organizations or other locations convenient to participants in 2013-2014. Results Women reported encountering an interconnected web of institutional processes that used racializing markers to infer legal status and eligibility to access health-promoting resources. Our findings highlight women's use of both individual and collective action to navigate exclusionary policies and processes, working to: (1) maintain access to health-promoting resources; (2) limit labeling and stigmatization; and (3) mitigate adverse impacts of immigrant policing on health and well-being. The strategies women engaged were shaped by both the immigration processes and structures they confronted, and the resources to which they had access to within their social network. Conclusions Our findings suggest a complex interplay of immigration-related policies and processes, social networks, and health-relevant resources. They highlight the importance of inclusive policies to promote health for immigrant communities. These findings illuminate women's agency in the context of structural violence facing immigrant women and are particularly salient in the face of anti-immigrant rhetoric and exclusionary immigration and immigrant policies.